Trends in antimicrobial resistance education research: a bibliometric analysis - Sara Farina; Gianluca Fevola; Andrea Adduci; Alessandra Maio; Alberto Lontano; Walter Ricciardi; Maria Rosaria Gualano; Leonardo Villani (One Health)
Background: Antimicrobial resistance (AMR) poses a severe public health threat, with educational interventions recognized as pivotal in mitigating its impact. The World Health Organization (WHO) Global Action Plan on AMR emphasizes awareness and education as fundamental strategies. Given the complex interplay between human, animal, and environmental health in the development and spread of AMR, educational initiatives are increasingly being framed within a One Health approach. This study aims to examine the scientific production on AMR education of healthcare professionals and the general population. Methods: A bibliometric analysis was performed on AMR education literature on the Web of Science Core Collection database up to December 2023. Using the Biblioshiny tool within the Bibliometrix R package, the analysis covered productivity metrics, citation impact, keyword co-occurrence, and thematic mapping. Results: The study analyzed 1124 documents published on AMR education between 1995 and 2023, with a 20.5 % annual growth in publications. Key journals included Antibiotics-Basel and PLOS ONE, while highly cited sources were Journal of Antimicrobial Chemotherapy and Clinical Infectious Diseases. The University of London and the US led in institutional and country contributions. Keywords like “knowledge”, “attitudes”, and “stewardship” were central, reflecting the focus on educational initiatives. Thematic evolution revealed significant growth, with the number of themes increasing from four in 1995–2008 to 20 by 2021–2023, demonstrating the dynamic and expanding nature of research in this field. Conclusions: The expansion of AMR education research reflects growing global commitment to combating AMR through targeted educational strategies. Framing AMR education within the One Health approach may enhance its effectiveness, by addressing the interconnected drivers of resistance across sectors. Our findings highlight the importance of sustaining international collaboration and aligning AMR educational efforts with national policies. Future research should emphasize interdisciplinary approaches and innovative methods to address the complex challenges of AMR across diverse populations.